2023
DOI: 10.1002/pol.20230283
|View full text |Cite
|
Sign up to set email alerts
|

Controlled, supramolecular polymer formulation to engineer hydrogels with tunable mechanical and dynamic properties

Martin G. T. A. Rutten,
Laura Rijns,
Patricia Y. W. Dankers

Abstract: Nature uses combined covalent (chemical bonds) and non‐covalent (physical bonds) synthesis in a highly, controlled multi‐step fashion to create functional materials with different mechanical and dynamic properties out of similar building blocks. Surprisingly, this control in fully synthetic systems remains elusive, even though the effects of formulation pathways on the assembly processes have been emphasized—highlighting the importance of and relationship between energy landscapes and function in synthetic sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Formulation of UPy and BTA Supramolecular Fibers and Hydrogels. A strict supramolecular formulation protocol was used to obtain supramolecular fibers and eventually hydrogels from solid monomers (see the Materials and Methods section for detailed procedure) 62 . In the UPy system, for dilute-state measurements (c < 500 μM), adequate amounts of M-UPy were weighed and dissolved in Milli-Q (MQ) water while heating at 70 °C, after which the mixture was briefly vortexed and cooled to room temperature to allow the formation of supramolecular UPy fibers.…”
Section: Resultsmentioning
confidence: 99%
“…Formulation of UPy and BTA Supramolecular Fibers and Hydrogels. A strict supramolecular formulation protocol was used to obtain supramolecular fibers and eventually hydrogels from solid monomers (see the Materials and Methods section for detailed procedure) 62 . In the UPy system, for dilute-state measurements (c < 500 μM), adequate amounts of M-UPy were weighed and dissolved in Milli-Q (MQ) water while heating at 70 °C, after which the mixture was briefly vortexed and cooled to room temperature to allow the formation of supramolecular UPy fibers.…”
Section: Resultsmentioning
confidence: 99%
“…Supramolecular interactions are arising as a very promising tool to create ECM mimics owing to their inherent dynamics, adaptability, and tunability. Bioactive function can easily be introduced through coupling bioactive cues to the monomeric building blocks and mixing these into the supramolecular assemblies. Supramolecular copolymerization can elegantly be used to tune not only the ligand presentation but also the fiber morphology and mechanical properties. , Varying the formulation of these molecules allows the formation of fibers, hydrogels, and solid meshes as well as the tuning of hydrogel properties. , Finally, the coassembly of individual systems into larger, hierarchical complexes with synergistic function might be key to recapitulate all important properties of the native ECM.…”
Section: Simplicity Enables Complexity; a Supramolecular Approachmentioning
confidence: 99%
“…From strong, persistent collagen I to the soft, transient collagen IV, a singular biopolymer can be given diverse function based on differences in assembly and post-translational modifications. While traditional covalent hydrogels often have hierarchical information imparted via processing steps, supramolecular hydrogels offer unique opportunities for providing diverse morphologies based on formulation and processing conditions. , Though the potential polymorphism during self-assembly of supramolecular assemblies can be a challenge, ,, gaining control and direction over this process has the potential to offer emergent properties from singular systems with high reproducibility rates, as also recently highlighted by Adams et al While a difficult area of research, new analytical tools and methodologies, like intermediate quality control steps, set this up to be a promising area of innovative structure–property relationships in the near future. Mechanoresponsiveness and complex, dynamic mechanical properties are abundant and important in natural systems. , In nature, for example, the Ruberti and Dunn groups have shown that the enzymatic degradation load of collagen is dependent on the applied mechanical force. , Likewise, fibrins’ bioactivity is regulated through a mechanochemical feedback loop; when fibrin is under mechanical stress, decreased binding of fibrin and platelets was observed, yielding less activated platelets . Hence, of particular interest in the future is the combination of supramolecular interactions with mechanoresponsive elements, such as Förster resonance energy transfer (FRET) sensors, as many ECM functions are regulated by cellular tension. Additionally, the introduction of complex mechanical features, like stress stiffening as observed in fibrin, remains challenging in synthetic supramolecular systems.…”
Section: Limitations and Considerationsmentioning
confidence: 99%
See 2 more Smart Citations